“Attraction of Place”: The Painting of Shoi Churuk and Oralbek Kaboke as Cultural Memory - Shaygozova, Zhanerke N.; Naurzbayeva, Almira B. (The New Research of Tuva, 2025)
The article analyzes the distinctive features of artistic expression of cultural memory in the works of Shoi Churuk (b. 1967) and Oralbek Kaboke (b. 1987), representatives of the pictorial schools of Tuva and Kazakhstan of the 21st century. The analysis is based on a close reading of selected paintings by the artists, fragments of which are used to illustrate the text.In the works of Shoi Churuk and Oralbek Kaboke, the central principle is an original pictorial engagement with the theme of the collective, contemporaries, and their memory. Their art seeks to assemble the dispersed affects of collective memory into a coherent visual and emotional whole. It is noted that although each artist demonstrates a highly individual style, both are united by a shared impulse toward the actualization of cultural memory.The painters’ works reflect a renewed understanding of the spiritual values of nomadic culture, which, through the lens of the idea of “attraction of place,” may be viewed as a search for a local and authentic artistic space. Their art is characterized by a specific method of encoding semantic contexts, a practice of deconstruction, and a philosophical discourse that shapes their intellectual axis. Furthermore, both artists present themselves as painter-scholars — codifiers of the sacred and the spiritual.
Keywords: art; nomadic aesthetics; artistic process; painting; Tuva; Tuvans; Kazakhstan; Kazakhs; Shoi Churuk; Oralbek Kaboke